Systemic impact molds mesenchymal stromal/stem cell aging. Issue 3 (June 2015) - Reitinger, Stephan; Schimke, Magdalena; Klepsch, Sebastian; de Sneeuw, Snezana; Yani, Stella Lukas; Gaßner, Robert; Ertl, Peter; Lepperdinger, Günter
Abstract: Aging is associated with an accruing emergence of non-functional tissues. Mesenchymal stem cells (MSC) bring forth progenitors with multi-lineage differentiation potential, yet, they also exhibit anti-inflammatory and tissue-protective properties. Due to aging, altered tissue microenvironments constrict controlled stem cell proliferation and progenitor differentiation, thus diminishing the fitness of MSC. Therefore, deepening our understanding of metabolic, molecular and environmental factors impacting on MSC during human aging as well as providing new vistas on their role in promoting healthy aging and preventing age-associated disease is pivot. It is anticipated that integrative quantification of systemic parameters dominantly impacting on MSC will also enable effective personalized prognosis and provision of effective early medical interventions. Working along this line, it can be envisaged that standards in medical therapies can be individually adjusted by accounting not solely for the patient's chronological age or other physical parameters rather than specific physiological parameters which are believed to functionally shape stem cell niches within the bone marrow.